(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the major characterization techniques employed by Geoffrey Chaucer in the General Prologue of The Canterbury Tales. Chaucer presents a diverse group of pilgrims representing various social classes, professions, and moral attitudes of fourteenth-century English society. The article analyzes how Chaucer combines direct and indirect characterization, physical description, social and occupational identity, irony, satire, humor, and contrast to create vivid and realistic portraits of his characters. Special attention is given to the ironic narrative voice and the use of symbolic details, which expose human weaknesses and social hypocrisy, particularly among religious figures.